An Overview of Digital Health in the Transition of Pediatric to Adult Epilepsy Care - Bernard-Willis, Ysabeau; Oliveira, Emily De; Lakhan, Shaheen E (Journal of Pediatric Epilepsy, 2020)
Children with epilepsy often have impairments in cognitive and behavioral functioning which may hinder socio-occupational well-being as they reach adulthood. Adolescents with epilepsy have the added worry of health problems while starting the transition from family-centered pediatric care into largely autonomous adult care. If this transition is not appropriately planned and resourced, it may result in medical mistrust, nonadherence, and worsening biopsychosocial health as an adult. In recent years, there has been increased availability of digital health solutions that may be used during this stark change in care and treating teams. The digital health landscape includes a wide variety of technologies meant to address challenges faced by patients, caregivers, medical professionals, and health care systems. These technologies include mobile health products and wearable devices (e.g., seizure monitors and trackers, smartphone passive data collection), digital therapeutics (e.g., cognitive/behavioral health management; digital speech–language therapy), telehealth services (e.g., teleneurology visits), and health information technology (e.g., electronic medical records with patient portals). Such digital health solutions may empower patients in their journey toward optimal brain health during the vulnerable period of pediatric to adult care transition. Further research is needed to validate and measure their impact on clinical outcomes, health economics, and quality of life.
Keywords: care transition; digital health; technology